The effect of WeChat-based brisk walking on kinesiophobia in patients after percutaneous coronary intervention: a randomised controlled trial - Wan, Bo-Ya; Zhou, Ce; Sun, Xing; Yu, Feng-Min; Liu, Mei-Xia; Zhang, Jia-Yuan; Li, Qi; Zhang, Li (Frontiers in Cardiovascular Medicine, 2025)
AimThis study aimed to evaluate the benefit of a home-based cardiac rehabilitation (CR) programme with telemonitoring guidance on kinesiophobia in patients with percutaneous coronary intervention (PCI) discharged from hospital. It also aimed to explore the effectiveness of this programme on self-efficacy and cardiorespiratory endurance using a randomised controlled trial.DesignThis study was a single-blind, prospective randomised controlled trial.MethodsPatients who underwent PCI at our hospital were enrolled. The intervention group (IG) performed WeChat-based brisk walking and the control group (CG) received the usual care, including advice to remain physically active. All patients underwent cardiopulmonary exercise testing to assess their peak oxygen uptake (peak VO2) at baseline and after a 12-week intervention period. The main outcome indicator was kinesiophobia. Secondary outcomes included exercise self-efficacy, cardiorespiratory endurance (i.e., peak VO2), and major adverse cardiovascular events.ResultsA total of 137 patients were enrolled in this study between 1 February 2023 and 31 October 2023. Of them, 130 patients successfully completed a 12-week WeChat-based brisk walking CR programme. After 12 weeks of intervention, the Tampa Scale for Kinesiophobia Heart scores in the IG decreased significantly more than in the CG and pre-IG. The IG's Self-Efficacy for Exercise scores were higher than those of the CG and pre-IG. In addition, the increase in peak VO2 was larger in the IG than in the CG.ConclusionThe WeChat-based brisk walking programme is beneficial for reducing kinesiophobia by increasing exercise self-efficacy in patients after PCI; it also helps to improve cardiopulmonary endurance. WeChat-based brisk walking is feasible and acceptable.